Seven-day dietary nitrate supplementation clinically significantly improves basal macrovascular function in postmenopausal women: a randomized, placebo-controlled, double-blind, crossover clinical trial - Delgado Spicuzza, Jocelyn M.; Gosalia, Jigar; Zhong, Liezhou; Bondonno, Catherine; Petersen, Kristina S.; De Souza, Mary Jane; Alipour, Elmira; Kim-Shapiro, Daniel B.; Somani, Yasina B.; Proctor, David N. (Frontiers in Nutrition, 2024)
Introduction Cardiovascular disease (CVD) is the leading cause of death in women, with increased risk following menopause. Dietary intake of beetroot juice and other plant-based nitrate-rich foods is a promising non-pharmacological strategy for increasing systemic nitric oxide and improving endothelial function in elderly populations. The purpose of this randomized, placebo-controlled, double-blind, crossover clinical trial was to determine the effects of short-term dietary nitrate (NO3−) supplementation, in the form of beetroot juice, on resting macrovascular endothelial function and endothelial resistance to whole-arm ischemia–reperfusion (IR) injury in postmenopausal women at two distinct stages of menopause. Methods Early-postmenopausal [1–6 years following their final menstrual period (FMP), n = 12] and late-postmenopausal (6+ years FMP, n = 12) women consumed nitrate-rich (400 mg NO3−/70 mL) and nitrate-depleted beetroot juice (approximately 40 mg NO3−/70 mL, placebo) daily for 7 days. Brachial artery flow-mediated dilation (FMD) was measured pre-supplementation (Day 0), and approximately 24 h after the last beetroot juice (BR) dose (Day 8, post-7-day BR). Consequently, FMD was measured immediately post-IR injury and 15 min later (recovery). Results Results of the linear mixed-effects model revealed a significantly greater increase in resting FMD with 7 days of BRnitrate compared to BRplacebo (mean difference of 2.21, 95% CI [0.082, 4.34], p = 0.042); however, neither treatment blunted the decline in post-IR injury FMD in either postmenopausal group. Our results suggest that 7-day BRnitrate-mediated endothelial protection is lost within the 24-h period following the final dose of BRnitrate. Conclusion Our findings demonstrate that nitrate-mediated postmenopausal endothelial protection is dependent on the timing of supplementation in relation to IR injury and chronobiological variations in dietary nitrate metabolism. Clinical trial registration https://classic.clinicaltrials.gov/ct2/show/NCT03644472